Problematika Penggunaan Fitur E-Learning 2 dan 3 di Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Padang pada Masa Pandemi Covid-19 - Ririn Febrianti; Aisiah Aisiah (PAMA Aksara, 2021)
The purpose of this study was to describe the obstacles felt by lecturers and students of the History Department, Faculty of Social Science, Universitas Negeri Padang in using the features contained in e-learning. The research is motivated by initial findings which show that there are various obstacles experienced by lecturers and students in utilizing and accessing the features available in Universitas Negeri Padang e-learning. This study uses a mixed-method. The results of the study indicate that the obstacles experienced by lecturers in utilizing e-learning features; detailed technical knowledge in managing certain features have not been mastered by lecturers. These features are the BigBlueButton, Chat, Choice, Glossary, Lesson, Quiz, Wiki, Book, Folder, Label, Page, and URL features (still limited in use; under 10%). The features that are commonly used by lecturers are the assignment, attendance, forum, and file features (utilization in the 10%-20% range). The obstacles in accessing e-learning that is felt by students, which are often errors, especially in the morning, do not know in detail the functions of each feature.